Comparison of arm circumference against standard anthropometric indices using data from a high density town near Harare, Zimbabwe - Siziya, Seter; Matchaba-Hove, Reginald (2016)
In a limited controlled sample, the performance of the middle upper arm circumference (MUAC) was compared to those of standard indices (weight for age, height for age and weight for height), using 90 children aged one to four years living in a high density town near Harare, Zimbabwe. Using a cut off point of 15,5 cm, the MUAC performed best in relation to the weight for age (sensitivity 66,7 pc (95 pc confidence interval (CI) 53,3-80,0 pc), specificity 76,2 pc (95 pc CI 61,7-80,5 pc)) than to any other standard index. Nevertheless, this performance was unsatisfactory because about 30 in every 100 (28,9 pc) children would have been inaccurately identified as healthy or diseased.